Antenatal diagnosis of trisomy 18, harm and parental choice - Wilkinson, J. C. (Journal of medical ethics, 2010)
In this commentary I assess the possible harms to a fetus with trisomy 18 of continued life. I argue that, although there is good reason to avoid subjecting infants to major surgery and prolonged intensive care where there is little chance of benefit, doctors should support and engage honestly with parents who decide to continue their pregnancies. We should ensure that infants with trisomy 18 have access to high quality palliative care.